Impelementasi Budaya Madrasah dalam Membangun Karakter Peserta Didik di MA Putri Al Ishlahiyyah Wonorejo - Eni Nafisah; Wahidmurni; Parmudjianto (EduInovasi: Journal of Basic Educational Studies, 2024)
Each Madrasah must create its own Madrasah Culture as its own identity and also as a sense of pride in its school. Madrasah culture refers to a system of shared life which is believed to be a norm or pattern of behavior that is shared together, which is expected to influence how Madrasah residents act and behave. This research aims to describe the implementation of Madrasah culture at MA Putri Al Islahiyyah Wonorejo and to determine its application in building the character of MA Putri Al Islahiyyah students. The results of this research show that MA Putri Al Islahiyyah implements 11 madrasa cultures which were developed in three programs, namely daily habituation programs, extracurricular programs and supporting programs. The implementation of culture at MA Putri Al Islahiyyah is expected to form religious character, discipline and good manners. , Democratic, creative, innovative, self-confident, critical reasoning, public speaking and care for the environment. The implementation of the MA Putri Al Ishlahiyyah culture did not run perfectly due to obstacles that hindered it, but this was anticipated with various efforts, including special guidance for students with problems and establishing good communication with student parents.